A Prospective Clinical Study on Blood Mercury Levels Following Endodontic Root-end Surgery with Amalgam - Saatchi, Masoud; Shadmehr, Elham; Talebi, Seyed Morteza; Nazeri, Mohsen (Iranian Endodontic Journal, 2013)
Introduction: The purpose of this clinical study was to compare the blood mercury levels before and after endodontic surgery using amalgam as a root-end filling material. Materials and Methods: Fourteen patients requiring periradicular surgery participated in this prospective clinical study. A zinc-free amalgam was employed as root-end filling material. Blood samples were collected at three intervals: immediately before, immediately after and one week postoperatively. Mercury content of the blood was determined using gold amalgamation cold-vapor atomic absorption spectrometry. Obtained data were analyzed using analysis of variance for repeated measures and paired t-test. Results: The mean (SD) of blood mercury levels was 2.20 (0.24) ng/mL immediately before surgery, 2.24 (0.28) ng/mL immediately after surgery and 2.44 (0.17) ng/mL one week after the periradicular surgery. The blood mercury level one week post-operative was significantly higher than both blood mercury levels immediately before (P<0.001) and immediately after (P=0.005) the surgery. Conclusion: Placement of an amalgam retroseal during endodontic surgery can increase blood mercury levels after one week. The mercury levels however, are still lower than the toxic mercury levels. We suggest using more suitable and biocompatible root-end filling materials.